COMMENTS ON GUIDELINES OF AMERICAN COLLEGE OF CARDIOLOGY, AMERICAN HEART ASSOCIATION AND EUROPEAN SOCIETY OF CARDIOLOGY (2006) FOR THE MANAGEMENT OF PATIENTS WITH ATRIAL FIBRILLATION - S. R. Gilyarevskiy (Столичная издательская компания, 2015)
Comments on Guidelines of American College of Cardiology, American Heart Association and European Society of Cardiology (2006) for the management of patients with atrial fibrillation.